Effect of substituting goat’s milk with cow’s milk in Crottin-type cheese (UNED Research Journal, 2026)
Introduction: Crottin-type cheese is traditionally made with goat’s milk, which gives it a distinctive sensory profile but may be too intense for some markets and more costly to produce; partial substitution with cow’s milk may support product diversification, sensory modulation, and cost reduction. Objective: We evaluated the effect of replacing goat’s milk with cow’s milk at 0%, 50%, and 100% on yield, physicochemical characteristics, texture, color, and sensory acceptance during storage. Methods: We determined yield after manufacture. On day three, we evaluated fat, protein, salt, and overall sensory acceptance; on days three and 22, we measured moisture, % ATECAL, pH, color, and texture. We assessed consumer acceptance with 124 participants and analyzed the results by cluster analysis. Results: Protein content was the only compositional variable that differed significantly among cheeses (p
Keywords: dairy products; quality; rheology; colorimetry; acceptance